Do Cover Crops and Corn Residue Removal Affect Soil Thermal Properties?. Issue 2 (18th April 2019) - Sindelar, Michael; Blanco-Canqui, Humberto; Jin, Virginia L.; Ferguson, Richard
Abstract : Core Ideas: Corn residue removal reduces soil thermal conductivity and volumetric heat capacity. Cover crops do not mitigate corn residue removal effects on thermal properties. Soil water content and soil bulk density are strong predictors of soil thermal properties. Soil thermal properties govern the transport and storage of heat in the soil. How management practices such as crop residue removal and cover crop (CC) use affect these soil properties is not well understood. For example, CCs could provide physical cover and improve soil properties after main crop residue removal and thus ameliorate the negative effects of residue removal on soil thermal properties. We measured changes in soil thermal properties including soil thermal conductivity, thermal diffusivity, volumetric heat capacity, and related properties under corn ( Zea mays L.) residue removal with and without winter cereal rye ( Secale cereale L.) under a 6‐yr irrigated no‐till continuous corn experiment on a silt loam in south central Nebraska. Cover crops did not affect thermal properties, but corn residue removal reduced field thermal conductivity by 12 to 41% and volumetric heat capacity by 6 to 49% during the growing season for the 0‐ to 5‐cm depth. Residue removal also reduced laboratory thermal conductivity by 19% at –0.03‐MPa and by 28% at –1.5‐MPa matric potential. Residue removal also reduced volumetric heat capacity in the laboratory by 23% at both matric potentials in the 0‐ to 10‐cm depth. Neither residue removal nor CC affected thermal diffusivity. Thermal conductivity was more strongly correlated with soil water content than with bulk density and soil organic C. Overall, CC had no effect on thermal properties, but corn residue removal could reduce the soil's ability to conduct heat relative to no removal.